2006
DOI: 10.1016/j.jacc.2005.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Tpeak-Tend and Tpeak-Tend Dispersion as Risk Factors for Ventricular Tachycardia/Ventricular Fibrillation in Patients With the Brugada Syndrome

Abstract: Our study demonstrates significant correlation between previous events, QTc >460 ms in V2, Tp-e, and Tp-e dispersion and occurrence of life-threatening arrhythmic events, suggesting that these parameters may be useful in risk stratification of patients with the Brugada syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
340
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 451 publications
(369 citation statements)
references
References 36 publications
7
340
1
1
Order By: Relevance
“…However, due to the fact that the RT interval is shorter than the QT interval, its variability is much reduced and, more importantly, the information provided by RT variability and QTV has been shown to be different in certain populations, such as in patients with cardiovascular diseases [77]. In relation to this, recent studies in the literature have shown that the interval between the apex and end of the T wave possesses variability that is independent from HR and which can provide clinically useful information to be used for arrhythmic risk stratification [78]. The methodology described in [42] considers a linear parametric model to quantify the interactions between QTV and HRV, being applicable under steady-state conditions.…”
Section: ) Qt Adaptation To Hr Changesmentioning
confidence: 99%
“…However, due to the fact that the RT interval is shorter than the QT interval, its variability is much reduced and, more importantly, the information provided by RT variability and QTV has been shown to be different in certain populations, such as in patients with cardiovascular diseases [77]. In relation to this, recent studies in the literature have shown that the interval between the apex and end of the T wave possesses variability that is independent from HR and which can provide clinically useful information to be used for arrhythmic risk stratification [78]. The methodology described in [42] considers a linear parametric model to quantify the interactions between QTV and HRV, being applicable under steady-state conditions.…”
Section: ) Qt Adaptation To Hr Changesmentioning
confidence: 99%
“…12) T peak -T end interval (T p-e ) is a well-known sensitive marker of spatial dispersion of ventricular repolarization. 13) A single observer manually measured T p-e of 5 consecutive beats, and the average was calculated. Clinical data: All 9 patients underwent echocardiography (Aplio XG ultrasonoscope, Toshiba Co., Tokyo) equipped with a 2.5-MHz transducer before starting the CR program.…”
Section: Methodsmentioning
confidence: 99%
“…The Tp-e interval was defined as the interval from the peak of T wave to the end of T wave ( Figure I). Measurements of Tp-e interval were performed from precordial leads as it was described [13]. T-wave peak to end interval, QT and RR intervals were measured by a computer based method.…”
Section: Measurement Of Tp-e Qt and Qrs Intervals From The 12-lead Ecgmentioning
confidence: 99%